Correlación ente mutaciones en el exón 15 del oncogén BRAF con distintas características histopatológicas y la evolución clínica de pacientes con melanoma cutáneo en diferentes estadios - Yepes Crow, Michelle Elizabeth (2015)
Cutaneous melanoma (CM) is the skin cancer with the higher increase in incidence. CM presents a high mutation rate, the most relevant nucleotide mutation is T1799A, resulting in the amino acid substitution V600E, in the BRAF oncogene. The serine-threonine protein kinase BRAFV600E is a constitutively active variant associated with cell proliferation involving the MAPK pathway. Among CM cell lines established in our laboratory there are BRAFV600E (8/16), BRAFV600K (4/16) and BRAFWT (4/16) variants. BRAFV600E cell lines present greater proliferative and clonogenic index in vitro. Recent studies performed in patients with regional metastases (AJCC stage III) reported a correlation between the presence of mutated BRAFV600 and a worse prognosis. The objective of this research was to determine the prevalence and status of BRAF mutations in tumor biopsies from a population of patients with CM in different stages (II, III, IV), all treated at the Instituto Alexander Fleming (n = 44), and their possible link with other clinico-pathological parameters. To do this, a methodology was established; DNA isolation from tumor biopsies fixed in formalin and embedded in paraffin; followed by the amplification of the region of interest and subsequent sequence analysis by the method of Sanger. Finally, BRAF mutational status of each biopsy was correlated to tumor clinico-pathologic characteristics.\nThe analyzed CM population presented a BRAFV600 oncogene mutation frequency of 77%, higher than that reported in bibliography which varies in the range 17-72%. We observed prevalence of BRAFV600E (98 %) mutation, followed by BRAFV600K (2%). The results obtained in the study population indicate that the mutated BRAF oncogene presents an association with some clinico-pathological parameters related to tumor progression, such as a Breslow thickness >2 mm in primary tumors (p=0,012), the presence of lymph node metastasis (p = 0,0036); and the proliferative index of metastatic tumors (p = 0,0353). No significant associations neither with other clinico-pathological characteristics nor with the clinical evolution were found. These results open the possibility of considering the BRAF oncogene mutational status as a prognostic factor, in order to improve staging of CM patients.